2010
DOI: 10.1371/journal.pgen.1000838
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Huntingtin Polyglutamine Stretch Enhances Neuronal Autophagy and Longevity in Mice

Abstract: Expansion of a stretch of polyglutamine in huntingtin (htt), the protein product of the IT15 gene, causes Huntington's disease (HD). Previous investigations into the role of the polyglutamine stretch (polyQ) in htt function have suggested that its length may modulate a normal htt function involved in regulating energy homeostasis. Here we show that expression of full-length htt lacking its polyglutamine stretch (ΔQ-htt) in a knockin mouse model for HD (Hdh140Q/ΔQ), reduces significantly neuropil mutant htt agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(118 citation statements)
references
References 67 publications
4
113
0
1
Order By: Relevance
“…S1B), a brain region that shows relatively early lipofuscin accumulation in aging rodents and for which dysfunction is implicated in HD (23,24). Lipofuscin and ubiquitin accumulation is similarly pronounced in striata from CAG140 HD mice (25,26). Although most Htt −/− mutants die before 15 mo of age because of hydrocephalus, in one surviving 2-y-old mutant mouse with milder hydrocephalus, ubiquitin and p62 puncta and lipofuscin accumulation were also prevalent in the striatum, similar to what we observed in 2-y-old 140Q/+ mouse striatum (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1B), a brain region that shows relatively early lipofuscin accumulation in aging rodents and for which dysfunction is implicated in HD (23,24). Lipofuscin and ubiquitin accumulation is similarly pronounced in striata from CAG140 HD mice (25,26). Although most Htt −/− mutants die before 15 mo of age because of hydrocephalus, in one surviving 2-y-old mutant mouse with milder hydrocephalus, ubiquitin and p62 puncta and lipofuscin accumulation were also prevalent in the striatum, similar to what we observed in 2-y-old 140Q/+ mouse striatum (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Brains were frozen and subjected to analysis as described in SI Materials and Methods. p62/SQSTM1 was detected by Western analysis in the striatal insoluble pellet fraction and quantitated as previously described (26).…”
Section: Methodsmentioning
confidence: 99%
“…For example, expression of full-length HTT lacking its polyQ (ΔQ-HTT) in a knock-in mouse model of HD increases autophagy markers and longevity. 65 In vitro expression of ΔQ-HTT also increases autophagosome synthesis and ATG5-dependent clearance of HTT aggregates. 65 In addition, a new study reported that WT-HTT serves as an important scaffold protein in multiple types of selective macroautophagy (not including starvation-induced autophagy) in Drosophila and mammalian cells (including mouse embryonic fibroblasts and striatal cells).…”
Section: 51mentioning
confidence: 99%
“…Two htt-interacting proteins, Rab5 and Rhes, are positive regulators of autophagy (73,74), and htt lacking the polyglutamine repeat region induces autophagy and is protective against toxicity of mutant polyglutamine-expanded htt in cells and mice (75), suggesting a more direct role for htt in autophagy.…”
Section: Autophagy In the Pathogenesis Of Neurodegenerative Diseasementioning
confidence: 99%